Clinical practice: The approach to the deaf or hard-of-hearing paediatric patient - Smeijers, Anika S. (Springer-Verlag, 2011)
Approximately 1 child in 1,000 is deaf or severely hard of hearing from birth, and the prevalence rises to about 1.6 per 1,000 in adolescents. Providing medical care for this group of children poses special challenges for professionals. To allow a medical consultation to proceed successfully and to the satisfaction of the patient, it is essential that physicians are aware of the different linguistic and cultural background of these patients. Healthcare workers should be aware of the possible higher incidence of comorbidities, sexual abuse and (psycho)social problems, of the possible pitfalls in obtaining informed consent and higher frequency of medical mistakes. This review describes the communication challenges and medical, ethical and legal issues a physician can experience when faced with these patients.